Ethnographie Des Pratiques De Sécurisation De L’accès Aux Ressources Agropastorales Dans Un Contexte De Conflits Entre Agriculteurs Et Migrants Eleveurs A Dianra (Côte d’Ivoire) - Jacques, Kouame Konan (European Scientific Journal, ESJ, 2016)
Climate variability and dwindling agro-pastoral resources are considered a threat to the stability of nations. Their environmental, economic, social and policies consequences on people behind this threat. The conflict farmers and ranchers is one of the consequences. In the northern Ivory Coast in general and in particular Dianra, the conflict between farmers and herders is not new. It is recurrent and sometimes violent. In this context of conflict and dwindling resources, one of the challenges is access to agropastoral resources, because despite these conflicts, indigenous farmers and migrant herders always co-operate the same space. There have been many writings on conflict farmers and ranchers. They aimed to understand the causes. In this study, our interest is less conflict. But the analysis we make is, how in the context of conflict, the user groups manage to secure access to resources. The study, conducted with fifty four (54) persons shows that in this context of conflict, access to resources is part of a dynamic interaction mobilizing various strategies to control and maintain access to resources: change of rules by the institutions of the dynamic layout, arrangements, handling of identity or professional referral and multiple use. If people develop coping strategies to different challenges offered by the changing context of their environment, it should be noted that these strategies highlight the social values of current changes in this environment.